AFFECTIVITY AND GAMIFICATION: THE APPLICABILITY OF THESE TWO CONCEPTS FOR IMPROVING THE LEARNING OF STUDENTS IN 9TH YEARS A AND B AT ESCOLA DONIZETTI APARECIDO LEITE - Monteiro Júnior, Walfrido (Revista Gênero e Interdisciplinaridade, 2023)
THEME: Affectivity and Learning. PROBLEM: How can the main concepts of affectivity and gamification contribute to the learning of Elementary School students (9th years A and B) at Escola Estadual Donizetti Aparecido Leite? GUIDING QUESTIONS? How to apply the concepts of affectivity to elementary school students at Donizetti Aparecido Leite State School? How can the relationship between affectivity and gamification contribute to improving student learning? How does gamification contribute to the applicability of affectivity in the classroom? HYPOTHESIS: does the applicability of the concepts of affectivity and gamification contribute to improving the learning of elementary school students (9th years A and B) at Escola Estadual Donizetti Aparecido Leite? SPECIFIC OBJECTIVES: Understand the main concepts of affectivity and gamification. Apply the main concepts of affectivity and gamification in the 9th grade classes A and B. Verify the relationship between the applicability of the main concepts of affectivity and gamification with the learning of the 9th grade classes A and B. METHODOLOGY: Quantitative and qualitative research was selected for the preparation of this article and the case study and field study as research methods.